(untitled) (International Journal of Environmental Sciences, 2025)
The concept of FPO’s being introduced by Dr Y K Alagh committee in their report submitted to government favoring the concept hybrid combination of cooperatives and companies. This concept is first being harnessed in Madhya Pradesh for increasing the income of farmers. Multistage sampling has been used for collecting the data. Data regarding key activities and status of 20 FPOs has been studied in this research paper which are further being divided in three stages Incubation or Nascent Stage FPO, Growing or Emergence stage FPO and Mature stage FPO. The chronbach alpha value has been used to test the reliability of questionnaire which is 0.72 and is acceptable. The study reveals distinct differences across nascent, growing, and mature FPOs in Madhya Pradesh. Nascent FPOs are mostly led by younger, less experienced female BoD’s and CEO’s with lower educational qualifications, limited landholdings, and basic activities like FIG formation and meetings. Growing FPOs have more experienced, male-dominated leadership, better educational background, cover more villages, and engage in advanced functions like training, marketing, and aggregation. Mature FPOs show improved turnover, perform value-added activities like processing and packaging, and have stronger market linkages. Resource support shifts from NGOs and SFAC in early stages to SRLM in mature ones, reflecting institutional evolution and growth.